Alat Bantu Jalan untuk Tuna Netra Menggunakan Sensor Ultrasonik - Sunardi; M. Amril Siregar; Agung Satria Wiguna; Iswandi idris; Rizaldy Khair (Manutech : Jurnal Teknologi Manufaktur, 2020)
The experience of sight is one in every of the essential sources of records for human beings. It is no exaggeration to say that the majority of human information comes from the sense of sight, while the rest comes from the other five senses. Therefore, it is understood that if a person experiences a sightrelated disruption, his activities will be very limited, because the information obtained is much less than typically visioned ones. Blind people typically use walking aids in the form of white canes or trained dogs to aid with balance and improve walking health and independence. The author will work out how the blind are more confident to navigate in a known setting by providing enough knowledge. To conquer these issues, an apparatus that can supplant and consummate the job of strolling sticks that made. The consequences of this investigation are as a gadget that can recognize objects utilizing an ultrasonic sensor that can peruse an article the extent that 2 meters as a separation and the ringer yields a sound yield.